PENGARUH STRATEGI THINKING ALOUD PAIR PROBLEM SOLVING (TAPPS) DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 10 PADANG - Nurfaida, Nurfaida; Delsi K, Delsi K; Melisa, Melisa (Pendidikan Matematika, 2014)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  ABSTRACTÂ This research was conducted as the students were unable to explain the way a problem solved and they got low understanding on mathematics concept. This research was aimed at revealing whether the conceptual understanding of the students taught by using Thinking Aloud Pair Problem Solving (TAPPS) assisted with quis was better than that of students taught by using conventional learning in class VIII of SMPN 10 Padang. This was an experimental research which applied random sampling technique. The instrument of the research were a quiz and a post-test which contained conceptual understanding indicators. The result of quis analysis indicated that the studentsâconseptual understanding improved from meeting I to meeting III and decreased in meeting IV. The result of hypothesis test by using t-test showed thatÂ  in which Â indicating that was accepted. Based on this result, it was concluded that the the conceptual understanding of the students taught by using Thinking Aloud Pair Problem Solving (TAPPS) assisted with quis was better than that of students taught by using conventional leraning in class VIII of SMPN 10 Padang.